Unravelling the molecular mechanism of TTL proteins in cellulose biosynthesis - García-Moreno, Álvaro (UMA Editorial, 2021)
Plants require mechanisms to sense and respond to the challenging environment, that encompass both biotic and abiotic factors that results in differential development. As cell walls shape plant growth, this differential growth response cause alterations to the plant cell wall (PCW) where cellulose is the major component. Therefore, understanding the mechanisms that regulate cellulose biosynthesis is essential to develop strategies to improve plant production. In Arabidopsis, the TETRATRICOPEPTIDE THIOREDOXIN-LIKE (TTL) gene family is composed by four members (TTL1 to TTL4) and mutations in TTL1, TTL3, and TTL4 genes cause reduced growth under salt and osmotic stress due to defects in PCW integrity. We observe association of TTL3 with most core components in traducing BR signalling, such as BRI1 or BIN2 that modulate cellulose biosynthesis. Whether the contribution of TTLs to the adaptation of the PCW during salt stress episodes, is mediated by their role in BR signalling, in other signalling pathways, or as scaffolding components remains elusive. As mentioned, mutations in TTL1, TTL3, and TTL4 cause reduced growth under abiotic stresses. Because ttl mutant growth is compromised during saline conditions, in this work we studied the role of TTL proteins in cellulose production, the major component of the PCW. In this thesis, we show that ttl mutants present defects in the PCW, particularly in isoxaben, salt or sucrose stress. Indeed, spinning disk microscopy in etiolated hypocotyls reveals that, TTL proteins are responsible for the Cellulose Synthase Complex (CSC) stability in plasma membrane upon salt or sucrose stress. Indeed, Y2H assays determine that TTL3 and TTL1 are new members of the CSC. Moreover, TTL3 associates with LRR-RLKs that have been shown to be important for cellulose biosynthesis such as FEI1 in the FEI1/FEI2/SOS5 pathway, however TTL function is independent of this pathway as spinning-disk microscopy revealed.
Keywords: Arabidopsis - Tesis doctorales; Celulosa - Tesis doctorales; Membrana celular - Tesis doctorales; Pared celular; Estrés abiótico; Membrana plasmática